Nilai-Nilai Pendidikan Islam Dalam Kisah Nabi Khiḍir dan Nabi Musa Berdasarkan Perspektif Deep Learning - wisnu susanto; Islah Gusmian (AL-IBANAH, 2026)
Education, as a continually evolving phenomenon, has adopted a deep learning approach, exemplified in the story of Prophet Khiḍir. This narrative emphasizes that learning involves profound experiences and reflection, rather than mere knowledge transfer. Through the events in the story of Prophet Musa and Khiḍir, it becomes evident how direct experiences can provide deeper meaning and understanding within the educational context. This study aims to identify essential elements of deep learning that can be integrated into the educational curriculum in Indonesia, while also addressing challenges in implementing the Merdeka curriculum. Utilizing a qualitative approach and analysis of the Quranic text, this research reveals the relevance of education within a religious context and underscores the importance of holistic learning. The findings indicate that the application of deep learning principles in the story of Prophet Khiḍir can offer new insights into the advancement of education for future generations.